1999
DOI: 10.1523/jneurosci.19-11-04200.1999
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Evidence against Apoptosis as the Mechanism of Neuronal Death in Global Ischemia

Abstract: It has been repeatedly claimed that neuronal death in the hippocampal CA1 sector after untreated global ischemia occurs via apoptosis. This is based largely on DNA laddering, nick end labeling, and light microscopy. Delineation of apoptosis requires fine structural examination to detect morphological events of cell death. We studied the light and ultrastructural characteristics of CA1 injury after 5 min of untreated global ischemia in gerbils. To increase the likelihood of apoptosis, some ischemic gerbils were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
156
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(181 citation statements)
references
References 52 publications
(70 reference statements)
20
156
5
Order By: Relevance
“…4). Similar morphological patterns of degenerating neurons were reported in the hippocampal region following global forebrain ischemia Colbourne et al, 1999). Therefore, hypoxic-ischemic insults to the brain appear to produce neuronal cell oncosis, possibly through mechanisms that involve excitotoxicity and oxidative stress (Table 1).…”
Section: Fas Receptorsupporting
confidence: 55%
“…4). Similar morphological patterns of degenerating neurons were reported in the hippocampal region following global forebrain ischemia Colbourne et al, 1999). Therefore, hypoxic-ischemic insults to the brain appear to produce neuronal cell oncosis, possibly through mechanisms that involve excitotoxicity and oxidative stress (Table 1).…”
Section: Fas Receptorsupporting
confidence: 55%
“…Since both necrosis and apoptosis are ongoing in ischemia, the separation of the two has been controversial (Colbourne et al, 1999) Caspases have been shown to be critical for programmed cell death in brain (Graham and Chen, 2001). Recently, we found that MPs may play an important role in facilitating the apoptotic process in brain.…”
Section: Endogenous Mmp Inhibitors: Tissue Inhibitors Of Metalloprotementioning
confidence: 99%
“…106,107 However, in the adult rat, delayed post-ischemic cell death prevented by hypothermia had a necrotic appearance on detailed electron microscopic criteria. 108 However, it is now clear that apoptotic mechanisms can be involved even in 'necrotic' cell death. Although multiple pathways are likely to be involved in such post-ischemic apoptosis, caspase-3, one of the family of cysteine proteases, is reported to play a crucial role.…”
Section: Suppression Of Apoptosis/ Programmed Cell Death?mentioning
confidence: 99%